Optimal dosage and modality of exercise on glycemic control in people with prediabetes: a systematic review and network meta-analysis - Zhang, Lin; Cheng, Xing; Yang, Yong; Li, Xue; Yuan, Yuan (Frontiers in Endocrinology, 2025)
AimsThis study aims to assess the effects of different exercise types and their specific doses on glycemic control among individuals with prediabetes.MethodsMultiple databases were subjected to a comprehensive search for randomized controlled trials (RCTs) published until 15 July 2024. The study protocol was prospectively registered with PROSPERO (CRD42024573186). The exercise interventions analyzed included aerobic exercise (AE), resistance training (RT), and combined aerobic–resistance training (AE+RT). Outcomes were quantified using standardized mean difference (SMD) with 95% credible intervals (CrIs), employing the confidence in network meta-analysis (CINeMA) framework for network meta-analysis to confirm the outcome reliability.ResultsAccording to the network meta-analysis, irrespective of dose, AE+RT led to the largest decrease in fasting blood glucose (FBG) (−0.44, [−0.62 to −0.26]). AE alone resulted in the largest reductions in 2-hour post-meal blood glucose (2hPG) (−0.71, [−0.97 to −0.45]) and glycosylated hemoglobin A1c (HbA1c) (−0.30, [−0.37 to −0.22]). Dose–response (DR) analysis identified optimal doses for each exercise type: 880 metabolic equivalent of task minutes per week (METs-min/week) for both AE and RT and 800 METs-min/week for AE+RT to reduce FBG. The optimal dose for 2hPG improvement via AE was 1,100 METs-min/week, and for HbA1c reduction via RT, it was 870 METs-min/week.ConclusionsGiven the variety of impaired glucose regulation (IGR), we recommend that people with prediabetes engage in RT at 1,100 METs-min/week to improve 2hPG and at 870 METs-min/week to reduce HbA1c. For FBG control, a dose of 800 METs-min/week is optimal for all exercise modalities. These evidence-based recommendations provide practical guidance for designing personalized exercise prescriptions to manage prediabetes.